A Review of Genetic Advances Related to Sex Control and Manipulation in Tilapia. Issue 2 (19th November 2017) - Chen, Jinlin; Fan, Zheng; Tan, Dejie; Jiang, Dongneng; Wang, Deshou
Abstract: Tilapias are the second most farmed fish worldwide. Production of tilapia has quadrupled over the past decade because of the ease with which they are cultured, their marketability, and the stability of market prices. Continued increases in tilapia production must be based on sustainable practices. Excessive reproduction during growout has been a major problem in tilapia aquaculture and has been addressed by culturing monosex (all‐male) populations. The best way to obtain monosex populations is through control of sexual development. To produce genetically male tilapia, researchers can arrange matings using sex‐specific DNA markers, create hybrids between tilapia strains with different sex determination loci, or they can alter the innate genetic traits of a species. Improved varieties have, in many cases, facilitated the development of the aquaculture industry by lowering costs and increasing both quality and yield. In this review, we focus on the application of marker‐assisted breeding, cross‐breeding, and genetic modification technologies to control sexual development in tilapia.